Pemberdayaan Masyarakat Desa Sidorejo dalam Menghadapi Pandemi Covid-19 di Era New Normal (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2021)
Human life around the world is changing, including Indonesia, especially the people of Sidorejo Village. This change is due to the Covid-19 virus which forces people to adopt a new daily life. In this case, globally, people's social life must be able to adapt to new conditions. Human life everywhere enters a space called the New Normal. This article wants to explain how to implement the new adaptation of the Sidorejo Village community. A social condition of the community or individual behavior to prevent the transmission of the Covid-19 virus.